CONCEPTUAL SPECIFICS AND PRACTICAL ASPECTS OF EFFECTIVE ORGANIZATION OF SCIENTIFIC-TECHNICAL NOVATION IMPLEMENTION PROCESS - S.M. HASHIN; A.E. SAFRONOV; V.V. KALUGINA (Advanced Engineering Research)
This article discloses the mechanism of creation, formation and realization of new scientific - and - technical innovations. They have an impact on size of economic effect from realization of new innovations.